Congenital Myasthenic Syndromes: Current Diagnostic and Therapeutic Approaches - Schara, Ulrike; Della Marina, Adela; Abicht, Angela (Neuropediatrics, 2012)
Congenital myasthenic syndromes (CMS) are rare genetically and clinically heterogeneous disorders characterized by an impaired neuromuscular transmission. Exact prevalence data are not available, approximately 2000 to 3000 patients worldwide have been diagnosed on a molecular level; mutations in 14 different genes are known to date leading to causal defects in presynaptic nerve terminal, synaptic cleft, and postsynaptic apparatus. At last, all known mutations are estimated to cause approximately 50% of all clinically diagnosed CMS. However, phenotypes may vary widely and symptoms can be unspecific, therefore CMS are often missed and their prevalence may be underestimated. But, the exact diagnosis is extremely important to start early appropriate therapy to prevent life-threatening events and to improve the clinical course. Most patients are eligible for drug therapy with esterase inhibitors, 3, 4-diaminopyridine, ephedrine, fluoxetine or quinidine, but the effect of these drugs differs depending on the underlying genetic defect. Moreover, very little is known about the best treatment and care in these patients over a longer period of time.This article provides an overview of specific clinical symptoms, diagnostic work-up, and care including possible pharmacotherapy in case of CMS.
Keywords: congenital myasthenic syndromes; phenotype; genotype; diagnostic work-up; therapeutic options; pharmacotherapy